Sistem Tracking Bola dengan Pembagian 3 Area menggunakan Metode Hough Circle Tranform berbasis Raspberry Pi - Yoga Sugma Pradana; Eko Setiawan; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
This study tries to do an in-depth video analysis using the hough circle transform method which will be applied to a camera slider so that it can detect and move automatically following an object in the form of an orange ball. The case study in this research is to replace the role of the football cameraman on the side of the field in taking close-up shots of the ball. This camera slider is controlled by a raspberry pi 3, a mini computer that is used to detect the ball and control the movement of the camera slider automatically. Image input comes from video input in the form of an orange ball with the help of the opencv library. The output of the results detected by the system is the coordinates of the center of the ball along with the distance of the ball. On the other hand, to facilitate the movement of the ball, the image frame is divided into 3 based on the x-axis. With the division value, area A starts from 0 - 120 pixels, area B starts from 121 - 160 pixels, area C starts from 161 - 320 pixels. To move the camera slider, it is driven by a dc motor at the end of the slider. The main function of the dc motor is to be able to follow the movement of the ball based on the position of the ball in the area A, B or C. While the camera slider position is placed on the side with the camera position facing the field. The size of the field in the study was reduced from its actual size to 1 meter x 2 meters. The camera slider can successfully detect the orange ball with a maximum detectable distance of 90 cm and the camera slider can move following the ball to the right, left and stops.